2013
DOI: 10.3390/nu5041253
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum 25-Hydroxyvitamin D Concentrations Associate with a Faster Recovery of Skeletal Muscle Strength after Muscular Injury

Abstract: The primary purpose of this study was to identify if serum 25-hydroxyvitamin D (25(OH)D) concentrations predict muscular weakness after intense exercise. We hypothesized that pre-exercise serum 25(OH)D concentrations inversely predict exercise-induced muscular weakness. Fourteen recreationally active adults participated in this study. Each subject had one leg randomly assigned as a control. The other leg performed an intense exercise protocol. Single-leg peak isometric force and blood 25(OH)D, aspartate and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 90 publications
5
95
0
Order By: Relevance
“…Our results are comparable with others showing that vitamin D levels are related with neuromuscular performance capacity and aerobic endurance in young physically active individuals and athletes [202][203][204][205]. However, these findings are not universal.…”
Section: Vitamin D Levels Athletes and Exercise Performancesupporting
confidence: 88%
“…Our results are comparable with others showing that vitamin D levels are related with neuromuscular performance capacity and aerobic endurance in young physically active individuals and athletes [202][203][204][205]. However, these findings are not universal.…”
Section: Vitamin D Levels Athletes and Exercise Performancesupporting
confidence: 88%
“…our results are comparable with a number of other reports on a variety of sports, all showing that vitamin D levels are closely associated with muscle power, neuromuscular performance and aerobic endurance in athletes. [110][111][112] of note, Hamilton et al 113 reported that vitamin D levels were not associated with lower limb isokinetic muscle function in soccer players, although those soccer players with lower levels of vitamin D exhibited a significantly lower torque in hamstring and quadriceps muscle groups compared to those with higher vitamin D levels, a finding suggesting that lower vitamin D levels are indeed associated with inferior muscular function during exercise.…”
Section: Vitamin D Levels and Indices Of Athletic Performance In Soccmentioning
confidence: 99%
“…In support of such a contention, is the finding that higher 25(OH)D concentration are associated with faster recovery from induced muscle injury. 28 Furthermore, a RCT of 28 healthy adults found 100 m day of vitamin D 3 enhanced the recovery in peak isometric force after a muscle-damaging event (P < 0.05). 29 In that study, supplemental vitamin D 3 attenuated (P < 0¢05) the immediate and delayed (2 day, 3 day and 7 day) increase in circulating biomarkers of muscle damage.…”
mentioning
confidence: 99%